The role of Painting in the Folk Art of Surkhandarya - Kamolov Iftikhor Bakhtiyorovich; Tilavov Askar Shodikulovich (Research Parks Publishers, 2021)
The article provides information on the history of pictorial art in the folk art of secondary school students. Students will understand that painting is an inseparable, unique and elegant field of visual and applied arts. Painting continues to develop from history to the present day, echoing us from the labyrinth